[Tobacco Institute and Coalition on Smoking and OR Health documents regarding the effect of excise taxes on employment] (Tufts Archival Research Center, 2007)
Collection of documents relating to claims by the Coalition on Smoking and OR Health that Price Waterhouse (PW) and Tobacco Institute (TI) estimates of the effect of an increase in cigarette tax on employment are false. Contains TI response that their findings can be backed up by Bakery, Cofectionary, and Tobacco Workers Union and that Coalition estimates are still significant. Includes Arthur Andersen report and Alan Davis statement accusing TI and PW statistics of being deliberately misleading.